Manifestations of symbolism in architecture of postmodernism - Mankus, Martynas (Journal of Architecture and Urbanism, 2014)
The article analyses expression of symbolism in Lithuanian postmodern architecture. It discusses the concept of symbolism and transformations of its meaning in comparison to the period of modernism as well as examines its most significant aspects in semantic understanding of postmodernist architecture. The article seeks to disclose the forms of symbolism represented in Lithuanian architecture by the end of the 20th – the beginning of the 21st century. It searches for the most expressive examples of Lithuanian architecture of the given period by clarifying the character of postmodernist use of symbols. Attempts have been made to trace the expression trajectories of symbolism in contemporary architecture that have been influenced by postmodernism.